Subjective Well-Being Approach to Environmental Valuation: Evidence for Greenhouse Gas Emissions - Beja, Edsel L, Jr (Archīum Ateneo, 2012)
The subjective well-being approach to environmental valuation is applied to analyze the valuation of greenhouse gas emissions with a fairness-adjustment in the valuation exercise. Results indicate that industrialized countries have high willingness-to-pay to reduce emissions. Developing countries differ in their valuations. Results indicate that poor countries have willingness to pay whereas middle income countries indicate willingness to accept payments to reduce emissions. Such high willingness-to-pay of industrialized countries, however, does not imply that they can pay off developing countries in order to continue emitting as usual. Still, the different positions with regard to emissions point to possibilities toward some inter-group payments and transfers system to allow societies to contribute toward global reduction emissions reduction.